Perinatal oral exposure to low doses of bisphenol A, S or F impairs immune functions at intestinal and systemic levels in female offspring mice - Yann Malaisé; Corinne Lencina; Christel Cartier; Maïwenn Olier; Sandrine Ménard; Laurence Guzylack-Piriou (BMC, 2020)
Abstract Background Bisphenol A (BPA), one of the highest-volume chemicals produced worldwide, has been identified as an endocrine disruptor. Many peer-reviewing studies have reported adverse effects of low dose BPA exposure, particularly during perinatal period (gestation and/or lactation). We previously demonstrated that perinatal oral exposure to BPA (via gavage of mothers during gestation and lactation) has long-term consequences on immune response and intestinal barrier functions. Due to its adverse effects on several developmental and physiological processes, BPA was removed from consumer products and replaced by chemical substitutes such as BPS or BPF, that are structurally similar and not well studied compare to BPA. Here, we aimed to compare perinatal oral exposure to these bisphenols (BPs) at two doses (5 and 50 μg/kg of body weight (BW)/day (d)) on immune response at intestinal and systemic levels in female offspring mice at adulthood (Post Natal Day PND70). Methods Pregnant female mice were orally exposed to BPA, BPS or BPF at 5 or 50 μg/kg BW/d from 15th day of gravidity to weaning of pups at Post-Natal Day (PND) 21. Humoral and cellular immune responses of adult offspring (PND70) were analysed at intestinal and systemic levels. Results In female offspring, perinatal oral BP exposure led to adverse effects on intestinal and systemic immune response that were dependant of the BP nature (A, S or F) and dose of exposure. Stronger impacts were observed with BPS at the dose of 5 μg/kg BW/d on inflammatory markers in feces associated with an increase of anti-E. coli IgG in plasma. BPA and BPF exposure induced prominent changes at low dose in offspring mice, in term of intestinal and systemic immune responses, provoking an intestinal and systemic Th1/Th17 inflammation. Conclusion These findings provide, for the first time, results of long-time consequences of BPA, S and F perinatal exposure by oral route on immune response in offspring mice. This work warns that it is mandatory to consider immune markers and dose exposure in risk assessment associated to new BPA's alternatives.